3D images of the silicone implants in capsular contracture after breast augmentation using magnetic resonance imaging with SPACE sequence. Issue 9 (September 2021) - Wang, Dawei; Ai, Tao; Xiong, Shixuan; Zeng, Ning; Wu, Min; Ren, Yuping; Wu, Yiping
Summary: Background: Capsular contracture is a common complication after breast augmentation. However, no objective methods are available to assess capsular contracture at present. The goal of the present study was to evaluate the correlation between capsular contracture and 3D images of the silicone implants by using magnetic resonance imaging (MRI) with sampling perfection with application optimized contrast using different flip angle evolutions (SPACE) sequence. Methods: Twenty-one patients (42 breasts) underwent breast augmentation, had postoperative MRI examinations with SPACE sequence, and the evaluation of the Baker grade by two trained plastic surgeons. Capsular thickness was measured on the T2-weighted images. The software ITK-SNAP was used to reconstruct 3D images of the implants. The fold characteristics such as number, depth, direction, and distribution were compared with the Baker grade. Results: Of the 42 breasts, 14, 8, 12, and 8 breasts were classified as Baker grade I, II, III, and IV, respectively. The MRI images of breasts with Baker grade III or IV revealed a thicker capsule (mean of 2.29 mm) as compared to the capsule with the lower Baker grades (mean of 1.58 mm). The 3D images of implants showed no difference in the number of folds between the groups with different Baker grades. The fold direction and fold distribution differed between grade I to II and grade III to IV. Conclusion: The 3D image of an implant with pathological folds is a potential and feasible diagnostic indication of capsular contracture. Level of Evidence: IV.